Efeitos do ultra-som terapêutico sobre o crescimento longitudinal do fêmur e da tíbia em ratos - Barreto, Alfredo Alcantara [UNESP]; Alcantara Barreto, Romi Kawasaki [UNESP]; Pereira, Hamilton da Rosa [UNESP]; Hosnne, William Saad [UNESP] (Atha Comunicacao & Editora, 2011)
Objectives: To determine the effects of ultrasound therapy on the femur and tibia growth in young rats. Method: Four-week-old male Ratus Norvegicus totaling 115 animals, divided into four groups, were submitted to ultrasound therapy (0.8 MHz, fixed tube head, continuous pulse, for 10 minutes, once a day, ten times) on the medial face of the right knee, with powers of 0.0 W/cm2 (group 31), 0.5 W/cm2 (group G2), 1.0 W/cm2 (group G3), and 1.5 W/cm2 (group G4). Histological slides of the epiphysis, growth plate and metaphysis and the femoral and tibial length measurements were studied in the sixth, thirteenth and twenty-sixth weeks of life. The data were submitted to factorial analysis of variance according to a one-way layout. Results: No statistically significant bone growth alteration was established between any of the three treated groups and the control group. However, alterations in femoral and tibial growth suggesting a decrease in G4 in relation to 02 and G3 were noted. In G4, histopathological alterations, such as cellular necrosis and post-necrosis bone neoformation were found. Conclusion: According to this study, no statistical evidence of bone growth stimulus or inhibition resulting from the application of ultrasound therapy was found when comparing the treated groups with the control group. Histological alterations regarded as pathological were only observed in G4. Also, smaller significant bone growth was found in G4 compared to G2 and G3. Level of Evidence: Level II, cross-sectional study.

OBJETIVO: Estudar efeitos do ultra-som terapêutico sobre o crescimento do fêmur e da tíbia, em ratos jovens. MÉTODO: Ratus norvegicus com quatro semanas de vida, machos, totalizando 115 animais, divididos em quatro grupos, foram submetidos ao ultra-som terapêutico (0,8 MHz, cabeçote fixo, pulso contínuo, por dez minutos, durante dez dias), na face medial do joelho direito, nas potências de 0,0 W/cm2 (grupo controle), 0,5 W/cm2 (grupo G2), 1,0 W/cm2 (grupo G3), e 1,5 W/cm2 (grupo G4). Lâminas histológicas da epífise, placa de crescimento e metáfise e as medidas dos comprimentos do fêmur e da tíbia foram estudadas na sexta, décima terceira e vigésima sexta semanas de vida. Os dados foram submetidos à análise de variância – fatorial inteiramente aleatorizado. RESULTADO: Nenhuma alteração estatística do crescimento ósseo foi estabelecida entre quaisquer dos três grupos tratados e o grupo controle. Entretanto, alterações sugestivas de diminuição do crescimento do fêmur e da tíbia de G4 em relação a G2 e G3, foram evidenciadas. No grupo G4 alterações histopatológicas como necroses celulares e neoformação óssea, pós-necrose, foram encontradas. CONCLUSÃO: Quando comparados os grupos tratados com o grupo controle, não há evidência estatística de estímulo ou inibição ao crescimento ósseo pela aplicação do ultra-som terapêutico. Nível de Evidência: Nível II, estudo coorte transversal.
Effects of therapeutic ultrasound on longitudinal growth of the femur and tibia in rats
Keywords: Ultrasound therapy; Bone development; Epiphyses; Rats